An Empirical Indifference Function for Income and Leisure - Dunn, L. F. (The Review of Economics and Statistics, 1978)
IN an earlier work, a survey technique has been developed for collecting and analyzing a set of subjective economic data in order to investigate the income-leisure preferences of a group of workers (Dunn, 1975). The marginal rates of substitution of wage income for leisure were obtained for a sample of low-income workers without using the competitive assumptions to equate them to existing wage rates. In the present paper we use these data to obtain an explicit indifference function obeying the axioms of transitivity and convexity, which is capable of reproducing our previous results. We find that the resulting labor supply curves are negatively sloped throughout the entire range of realistic wage rates.